Effectiveness of Tangent Equation Curve Learning through GeoGebra Software Assisted Module to Improve Students Creative Mathematical Thinking Skills - Nurjannah, Nurjannah; Subianto, Muhammad; Abidin, Zainal (International Journal for Educational and Vocational Studies, 2019)
The Curriculum of 2013 mandates that learning carried out by teachers in the classroom can foster a high-level thinking process including the ability to think creatively. Modules that can help creative students have been developed but not as good as the help of the GeoGebra Software module that can promote students creative thinking. This research focuses on the effectiveness of the tangent equation curve module GeoGebra Software assisted which aimed to make the students have the ability to think creatively. The subjects of the research were students of class XI of SMA 3 Banda Aceh. The instruments carried out in this research were creative thinking questions and observation sheets. Data analysis was performed by using descriptive analysis techniques. This research showed that the students' mathematical creative thinking ability was 85.98% which included in very good and good category, and overall student activity reached 91.1%. it means that the activities of students have run well. In conclusion, the teachers and students can use this module to improve mathematical creative thinking skills and the interest of students in learning mathematics assisted by GeoGebra software.